Attitudes towards female managers in hospitals: Case study of Turkey. (15th December 2020) - Kutlu, Gamze; Akbulut, Yasemin
ABSTRACT: Health sector is the one of the main fields of work for females; yet they are underrepresented in senior management positions. This study was conducted to evaluate the attitudes of hospital staff towards female managers in a state hospital in Ankara and also to determine the variation in attitudes according to socio-demographic and occupational characteristics of the employees. Attitude towards Women Managers Scale, developed by Berkman (2005), was used. The sample consisted of a total of 348 subjects including managers, physicians, nurses, and other healthcare staff. The study found significant differences in the total scores of attitudes towards female managers between male and female subjects. The differences in attitude scores "work ethic" dimension regarding the total working time and working title were statistically found. Employees with 16 years and above at work also the technicians& administrative staff had a more unfavourable attitude towards female managers. Regarding the level of education, employees with a high school education had the most unfavourable attitude in the "professional behaviour" dimension. Results indicated that hospital management can develop institutional policies addressing social gender equality, implement training programmes and projects to promote positive attitudinal changes among employees especially towards female ones.